Pembelajaran Mural pada Mata Pelajaran Seni Budaya di Sekolah Menengah Atas Negeri 10 Malang - Farida Hayati (Mahesa Research Center, 2022)
This article examines the emotional, intellectual, physical, aesthetic, artistic, and creative experiences of students at SMAN 10 Malang City. Students are directly involved in various creative experiences, producing works of art. Their real experiences directly benefit their lives. Learning mural art in the Cultural Arts subject allows students to interact with their technical abilities and environmental conditions. Murals are works of art that use drawing or painting techniques on permanent walls, walls or large surfaces. The purpose of this study is to examine the process of painting murals, considering that learning activities are believed to increase the intelligence of students, because the learning process involves cognitive, affective and psychomotor. The research method uses qualitative descriptive, the data used is student actions in the process of creating murals for class XII MIPA D students for the 2018-2019 school year. The analytical tools are observing, observing and recording student activities, as well as analyzing the work produced. The results of the study show that mural work is an alternative for teachers to increase students' creativity which is varied, namely 1) creative ideas, 2) reflection of students' emotional experiences, and 3) responsiveness to space.